(untitled) (Global Journal of Management and Business Research, 2019)
In such a highly competitive environment and competing with large resource-based firms, the competitive advantage lies in the ability of businesses, especially SMEs, to embrace the entrepreneurial innovation strategy. The purpose of this work is the explanation of entrepreneurial self-efficacy on entrepreneurial innovation of SMEs. To do this, we started from a theoretical framework to formulate the hypotheses that will be tested through a quantitative approach. Multiple regression analysis shows that the model is globally significant. Indeed, the ability to define the fundamental purpose, human and conceptual competence, the ability to recognize opportunities and the ability to financially manage determine positively the entrepreneurial innovation of SMEs. However, the ability to formally plan is not significant.